(untitled) (AN-ICON. Studies in Environmental Images [ISSN 2785-7433], 2023)
The paper focuses on exhibition practice, taking exhibitions as the key to contemporaneity. I will make a strong plea for the mutuality between past and present, the encouragement of visitors becoming participants through soliciting affective empathic attitude, and the accommodation to make this possible thanks to the enticement of durational looking. I will do this through the theoretical analysis of what exhibiting means and does, and through a consideration of my recent video installation Don Quijote: Sad Countenances. One episode of this project will be the hook on which to hang my view of art-making as, not an illustration of but a method of cultural analysis.